Analysis of verbal peer feedback in high school physical education - Brasil, Kimberley (My University, 2012)
The purpose of this study was to determine the frequency of verbal peer feedback amongst high school students (N=27) in an adventure education unit and compare it to the frequency of verbal peer feedback in a sport-specific unit. All verbal feedback heard by the principal investigator was tallied for a total of ten classes - five lessons from an adventure education unit (Rock Climbing) and five from a sport-specific unit (Badminton). Feedback was categorized by performance feedback, motivation feedback, and suggestive feedback. Motivation feedback was additionally categorized by positive motivation feedback and negative motivation feedback. The results of the independent samples t-tests comparing performance and motivation feedback in the two different environments showed no statistical difference (performance feedback, p-value = .157 and motivation feedback, p-value = .806). Similarly, no statistical difference was found for suggestive feedback in the two different environments using the non-parametric independent samples Mann-Whitney test (p-value = .044). In addition to these results, the independent samples t-tests comparing positive motivation and negative motivation feedback showed no statistically difference (positive motivation feedback, p-value =.173 and negative motivation feedback, p-value = .122).
Keywords: Physical education - Study and teaching